(untitled) (Herald of Journalism, 2022)
This article examines the history of publishing activities of one of the leading countries in this in- dustry – the United States. Here we speak about the first American types of press, about the printing house, about the history of the first publishers. Information is given about the scientific and public figure, the distinguished publisher and printer – B. Franklin, as well as the first American printing houses – Ste- phen and Matthew Dave. The formation of the first professional organizations devoted to improving the publications of the 19th century and stabilizing prices, such as the Boston Booksellers Association, the Philadelphia Book Trade Company, and the Bookselling Company of America, is analyzed. Also in the article it is noted that in America the publishing houses of universities occupy a special place, and many of these publishing houses are united in the organization – “University publishers”. Information is given on the systematization of American publishing houses by type of ownership and on various methods of book distribution.